A Review of Cooperative Learning in Chinese College English Classroom Teaching - Xiaobao, Han; Siti Maftuhah, Damio; Geethanjali, Narayanan (UNIMAS Publisher, 2022)
In many parts of college English instruction, cooperative learning (CL) has been used; it has numerous benefits, and many professors and students in China prefer it. However, despite the extensive use of CL in college English classes, there are still multiple issues and dilemmas. More research into its practical application is required to reap the benefits of CL and enhance students' holistic development. The key results of a review of CL include that teachers must comprehend students' genuine requirements and the issues they face in learning and give full play to the role of teachers' effective intervention in both online and offline CL.